Analysis of a Preimplantation Genetic Test for Aneuploidies in Embryos from Colombian Couples: A Report of Cases - D Cárdenas-Nieto; M Forero-Castro; H Moreno-Ortiz; E Lucena-Quevedo; J Cuzzi; C Esteban-Pérez (JRI, 2020)
Background: Assisted reproduction techniques (ARTs) and the preimplantation genetic test for aneuploidies (PGT-A) help couples with fertility problems to achieve a healthy live birth around the world. The aim of this study was to determine the rate of whole chromosomal copy number variations in embryos from couples undergoing ART and PGT-A, associations of chromosomal variations with embryo morphological parameters, and their relationship to maternal age. Methods: This study included a retrospective analysis of the number of whole chromosomal copies identified by aCGH in embryos from couples undergoing ART. Results: Seventy-six embryos from 29 couples using their own gametes were analyzed, of which 25 (32.9%) were chromosomally normal, and 51 (67.1%) were abnormal. Eleven embryos were evaluated from the group of couples with donated gametes, of which 5 (45.4%) embryos were chromosomally normal, and 6 (54.5%) embryos were abnormal. The main aneuploidies observed were trisomy X (7.8%), trisomy 21 (5.9%), trisomy 9 (3.9%), monosomy 11 (3.9%), monosomy 13 (3.9%) and monosomy X (3.9%), and the principal chromosomes affected were 19, X and 13. A significant association was found between the quality of the embryo and the genetic condition: embryos with euploidy and aneuploidy (p=0.046). Conclusion: The rate of aneuploidies from couples with their own gametes was 67.1% (51/76) and from couples with donated eggs and / or sperm was 54.5% (6/11). The quality of the embryo determinated by the morphological parameters was not associated with the embryo genetic status, and also there was no association between maternal age and aneuploidy rate.